1997
DOI: 10.2527/1997.752566x
|View full text |Cite
|
Sign up to set email alerts
|

Control of intramammary infections in goats: impact on somatic cell counts.

Abstract: Udder-half infections were recorded throughout a lactation for 1,060 goats belonging to eight commercial herds. Bacteriological examination from aseptic milk samples and somatic cell counts (SCC) determined by Fossomatic cell counting were performed at the beginning, the middle, and the end of lactation. Coagulase-negative staphylococci (CNS) were the prevalent microorganisms isolated. Geometric means of SCC for uninfected halves or halves infected by CNS or major pathogens were 272 x 10(3) cells/mL, 932,000 x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 14 publications
4
36
0
4
Order By: Relevance
“…Nesse estudo, SCN foram as bactérias mais freqüen-tes, concordando com os resultados obtidos anteriormente em outros trabalhos que afirmam que os SCN são os principais agentes isolados na mastite subclínica em caprinos (Mota et al 2000, Muricy 2003. Essas bactérias apresentam importância epidemiológica, pois podem causar mastite subclínica durante toda a lactação ou mesmo no período seco (Poutrel et al 1997), tornando os animais infectados fontes de infecção em potencial no rebanho. Some-se a isso a importância econômica desses agentes, que causam prejuízos aos produtores principalmente devido à redução na produção de leite (Leitner et al 2004).…”
Section: Resultsunclassified
“…Nesse estudo, SCN foram as bactérias mais freqüen-tes, concordando com os resultados obtidos anteriormente em outros trabalhos que afirmam que os SCN são os principais agentes isolados na mastite subclínica em caprinos (Mota et al 2000, Muricy 2003. Essas bactérias apresentam importância epidemiológica, pois podem causar mastite subclínica durante toda a lactação ou mesmo no período seco (Poutrel et al 1997), tornando os animais infectados fontes de infecção em potencial no rebanho. Some-se a isso a importância econômica desses agentes, que causam prejuízos aos produtores principalmente devido à redução na produção de leite (Leitner et al 2004).…”
Section: Resultsunclassified
“…Entretanto, apenas 37 (15,6%) apresentaram contagem maior ou igual a 5 UFC/0,01mL de leite (Contreras et al 1996). Staphylococcus coagulase negativo (SCN) foi identificado em 31 (83,8%) amostras, concordando com os resultados de estudos similares conduzidos no Brasil (Mota et al 2000, Muricy 2003) e em outros países (Hunter 1984, Lerondelle & Poutrel 1984, East et al 1987, Ryan & Greenwood 1990, Maisi & Riipinem 1991, Idrissi et al 1994, Contreras et al 1997, Poutrel et al 1997, White & Hinckley 1999, Winter & Baumgartner 1999. O predomínio de SCN poderia ser justificado pela presença destas bactérias na microbiota da pele e conjuntiva dos animais, particularmente no úbere de fêmeas leiteiras (Moroni et al 2005).…”
Section: Resultsunclassified
“…The dry period is wellacknowledged as being the optimal time to cure existing IMIs (22) as well as being a period of high risk for the acquisition of new IMIs (23,24). Thus, several authors (10,25) concluded that systematic and/or intramammary antibiotic treatment of goats at drying off is an efficient method for the reduction of subclinical mastitis. Poutrel et al (10) recommend systematic treatment when SCC in bulk milk is high (>1.000 × 10 3 cells mL -1 ) and when CoNS are involved in IMI.…”
Section: Referencesmentioning
confidence: 99%
“…Thus, several authors (10,25) concluded that systematic and/or intramammary antibiotic treatment of goats at drying off is an efficient method for the reduction of subclinical mastitis. Poutrel et al (10) recommend systematic treatment when SCC in bulk milk is high (>1.000 × 10 3 cells mL -1 ) and when CoNS are involved in IMI.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation